The multi-faceted potential of plant-derived metabolites as antimicrobial agents against multidrug-resistant pathogens. (March 2018) - Shin, Jonghoon; Prabhakaran, Vasantha-Srinivasan; Kim, Kwang-sun
Abstract: Multidrug-resistant (MDR) pathogens are currently causing serious problems globally in the medical setting. Improper and extensive usage of antibiotics results in a selective pressure supporting the rise of antibiotic-resistant microbes. Many key cellular bacterial components, including enzymes and small noncoding RNAs (sRNAs), and their involvement in MDR have been well studied, but exploiting such components in eradicating these pathogens requires further study. Delineation of many mechanisms that underpin the known MDR pathways necessitates urgent development of new specific strategies to control the rise of MDR pathogens. Botanical derivatives are comparatively safer than currently used antibiotics and exert multiple therapeutic benefits associated with their high efficacy. Numerous plant-derived compounds display synergistic activity with antibiotics against many MDR pathogens. Such plant derivatives include alkaloids, flavonoids, terpenoids, and tannins. A synthetic biological approach, e.g., metabolic engineering of secondary metabolites, can be utilized to exploit the natural metabolic pathways against MDR microbes. In this review, we focused on the major threats of antibiotic resistance, and the utilization of plant-derived compounds as alternative therapeutic agents to limit the rise of MDR pathogens. Highlights: Surge in microbial antibiotic resistance linked to antibiotic misuse is reviewed. Major antibiotic resistance mechanisms, and the role of sRNAs, are highlighted. Novel plant-derived phytochemicals with antimicrobial properties are summarized. Current metabolite engineering of phytochemicals against MDR microbes is discussed. Synergy of phytochemicals with multiple available antibiotics is appraised.